LEGAL STUDY CONCERNING PROVISION ON THE DEVELOPMENT OF ENVIRONMENTAL FUNDS IN DEVELOPMENT OF PUBLIC FACILITIES AND INFRASTRUCTURE IN THE DEVELOPMENT OF BUILDING STORAGE OF EVIDENCE GOODS AND HOUSEHOLD RESISTANCE OF NORTH SUMATRA AREA - Junaedi Junaedi (Fakultas Hukum Universitas Komputer Indonesia, 2020)
BUMN as a red template institution has long carried out a program that has similarities with the vision and mission of CSR which is a translation of the TJSL even though there were no regulations that obliged SOEs to do so. Potential donations to the public through PKBL are expected to provide greater benefits than those carried out by non-SOE corporations. Through the PKBL it is hoped that there will be an increase in the contribution of SOEs to the empowerment of the potential and condition of a synergic economic, social and environmental community so as to create equitable development. Besides having the main function of looking for profit, BUMN also has the duty to pay attention to social issues. In Article 88 paragraph (1) of Law No: 19 of 2003 concerning SOEs it is stated